Real-World Experiences in Autistic Adult Diagnostic Services and Post-diagnostic Support and Alignment with Services Guidelines: Results from the ASDEU Study - Scattoni Maria Luisa; Micai Martina; Ciaramella Antonio; Salvitti Tommaso; Fulceri Francesca; Fatta Laura Maria; Poustka Luise; Diehm Robert; Iskrov Georgi; Stefanov Rumen; Guillon Quentin; Rogé Bernadette; et al. (SPRINGER/PLENUM PUBLISHERS, 2022)
Research providing an evidence-base for autistic adult services is sparse. The Autism Spectrum Disorders in the European Union (ASDEU) network implemented an on-line survey to determine gaps in autistic adult diagnostic evaluation and post-diagnostic support services. More than 55% in all groups experienced most of the recommended features for diagnostic evaluation for autistic adults. In contrast, < 2% of adults or carers, and < 21% of professionals experienced each of the recommended features for post-diagnostic support. In contrast to 61% of professionals, only about 30% of autistic adults and carers had knowledge of good local services models for autism diagnosis in adulthood. There are major differences between good practice guidelines for diagnostic and post-diagnostic care for autistic adults, and what is actually experienced by services users and professionals.